Attitude of Responsibility of Prospective Counselors in Utilizing Internet Technology - Yaumas, Nova Erlina; Syafril, Syafrimen (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2019)
Students in the Department of Guidance and counseling are prospective education counselors who need to be given information about the use of internet technology that is good and right. The attitude of student responsibility needs to be known by educators so that educators can provide services to instill the attitude of student responsibility in the use of internet technology. This study aims to see the responsible attitude of prospective counselors in the use of internet technology in students of Guidance and Counseling. Research conducted through a qualitative approach, which refers to the case study research design. Potential Guidance and Counseling teachers who are also prospective counselors at the Faculty of Tarbiyah and teacher training at UIN Raden Intan Lampung became the subject of research. The research data were analyzed in a descriptive thematic way using Nvivo software. The results showed that there were still students who were not responsible for utilizing internet technology properly. Educators must provide motivation and direct students to have a more responsible attitude to use the Internet as a student's responsibility